Intracerebral schwannoma: CT and MR findings. - Di Biasi, C; Trasimeni, G; Iannilli, M; Polettini, E; Gualdi, G F (American Journal of Neuroradiology, 1994)
A case of intracerebral schwannoma in a 19-year-old man is reported. CT and MR findings were nonspecific, suggesting a primary glioma. The histologic features were of schwannoma.